Murine Intraepithelial Dendritic Cells Interact With Phagocytic Cells During Aspergillus fumigatus-Induced Inflammation - Bogorodskiy, Andrey O.; Bolkhovitina, Elena L.; Gensch, Thomas; Troyanova, Natalia I.; Mishin, Alexey V.; Okhrimenko, Ivan S.; Braun, Armin; Spies, Emma; Gordeliy, Valentin I.; Sapozhnikov, Alexander M.; Borshchevskiy, Valentin I.; Shevchenko, Marina A. (Frontiers in Immunology, 2020)
People are constantly exposed to airborne fungal spores, including Aspergillus fumigatus conidia that can cause life-threatening conditions in immunocompromised patients or acute exacerbations in allergics. However, immunocompetent hosts do not exhibit mycoses or systemic inflammation, due to the sufficient but not excessive antifungal immune response that prevent fungal invasion. Intraepithelial dendritic cells (IE-DCs) of the conducting airway mucosa are located in the primary site of the inhalant pathogen entry; these cells can sense A. fumigatus conidia and maintain homeostasis. The mechanisms by which IE-DCs contribute to regulating the antifungal immune response and controlling conidia dissemination are not understood. To clarify the role of IE-DCs in the balance between pathogen sensing and immune tolerance we investigated the A. fumigatus conidia distribution in optically cleared mouse lungs and estimated the kinetics of the local phagocytic response during the course of inflammation. MHCII+ antigen-presenting cells, including CD11c+ IE-DCs, and CD11b+ phagocytes were identified by immunohistochemistry and three-dimensional fluorescence confocal laser-scanning microscopy of conducting airway whole-mounts. Application of A. fumigatus conidia increased the number of CD11b+ phagocytes in the conducting airway mucosa and induced the trafficking of these cells through the conducting airway wall to the luminal side of the epithelium. Some CD11b+ phagocytes internalized conidia in the conducting airway lumen. During the migration through the airway wall, CD11b+ phagocytes formed clusters. Permanently located in the airway wall IE-DCs contacted both single CD11b+ phagocytes and clusters. Based on the spatiotemporal characteristics of the interactions between IE-DCs and CD11b+ phagocytes, we provide a novel anatomical rationale for the contribution of IE-DCs to controlling the excessive phagocyte-mediated immune response rather than participating in pathogen uptake.